Google it! Using the Google Trends tool to understand the Algarve Tourist destination public interest - G. Dinis; C. Costa; O. Pacheco (Dos Algarves, 2015)
In a sector strongly dependent on information as is the case of tourism, the timely knowledge of consumer behaviour enables making well-considered decisions and less uncertainty. Nowadays, the act of searching on the Internet about a particular subject before decision-making is part of the individuals’ daily lives. The Google Trends tool provides real time aggregated data on the online individuals’ interest based on the carried out search queries on Google. The objective of this paper is to show that Google Trends can provide comparative information about the individuals’ interest in relation to Portugal tourism regional areas and in particular, on the tourist destination "Algarve", and also between its competing tourist destinations. The results show that the tool can contribute to the knowledge of the individuals’ interests in relation to regional tourist destinations, information considered of great interest for Destination Management Organizations.